Periodization of Ethiopian History: Reflections, Questions, and some Modest Suggestions - Steven Kaplan (Aethiopica)
Historians have for many decades struggled with issues of periodization. In comparison to many other regions, scholars of Ethiopian history, particularly after the Aksumite period, have written comparatively little on this subject. This article considers some of the weaknesses of periodizations based on dynastic change or periods of a strong central state. It also suggests that attention to gender, class, geography, and ethnicity may assist in formulating, but also complicate periodizations.